THE POPULATION GENETICS OF SPOROPHYTIC SELF‐INCOMPATIBILITY IN THREE HYBRIDIZING SENECIO (ASTERACEAE) SPECIES WITH CONTRASTING POPULATION HISTORIES. (14th January 2013) - Brennan, Adrian C.; Harris, Stephen A.; Hiscock, Simon J.
<x xml:space="preserve">Abstract</x> Hybridization generates evolutionary novelty and spreads adaptive variation. By promoting outcrossing, plant self‐incompatibility (SI) systems also favor interspecific hybridization because the S locus is under strong negative frequency‐dependent balancing selection. This study investigates the SI mating systems of three hybridizing Senecio species with contrasting population histories. Senecio aethnensis and S. chrysanthemifolius native to Sicily, form a hybrid zone at intermediate altitudes on Mount Etna, and their neo‐homoploid hybrid species, S. squalidus, has colonized disturbed urban habitats in the UK during the last 150 years. We show that all three species express sporophytic SI (SSI), where pollen incompatibility is controlled by the diploid parental genome, and that SSI is inherited and functions normally in hybrids. Large‐scale crossing studies of wild sampled populations allowed direct comparison of SSI between species and found that the main impacts of colonization in S. squalidus compared to Sicilian Senecio was a reduced number of S alleles, increased S allele frequencies, and increased interpopulation S allele sharing. In general, many S alleles were shared between species and the S locus showed reduced intra‐ and interspecific population genetic structure compared to molecular genetic markers, indicative of enhanced effective gene flow due to balancing selection.